Teaching quality - Girón, Cosette (2020)
A quality management system on education is considered one of the main factors of social development in a country. Educational culture involves not only ensure quality in education, but also family habits and parenting. Teachers are a key in the educational development process. It is important in this process to have short cycles of self-learning, reinforcing both hard and soft competences. International quality standards in learning ensures an adequate quality management on educational processes, in which ethics represents a fundamental feature.